Clinical characteristics of undifferentiated pleomorphic sarcoma of bone and the impact of adjuvant chemotherapy on the affected patients: a population-based cohort study. (19th February 2022) - Kobayashi, Hiroshi; Zhang, Liuzhe; Hirai, Toshihide; Tsuda, Yusuke; Ikegami, Masachika; Tanaka, Sakae
Abstract: Background: Clinical characteristics of undifferentiated pleomorphic sarcoma of bone are not elucidated. Herein, we clarify its clinical features and analyze the efficacy of adjuvant chemotherapy in patients with undifferentiated pleomorphic sarcoma of bone. Methods: Prognostic factors and estimated disease-specific survival in 247 patients with primary undifferentiated pleomorphic sarcoma of bone were identified from a registry in Japan. The effect of adjuvant chemotherapy was evaluated in localized resectable cases, and the characteristics of the two groups treated with or without chemotherapy were adjusted using propensity score matching. Results: The 5-year disease-specific survival rates were 47.4% in the entire cohort and 56.4 and 16.9% in the M0 and M1 groups, respectively. Multivariate disease-specific survival analysis revealed that metastasis on initial presentation and age ≥ 65 years were poor prognostic factors. Overall, 132 localized and resectable primary lesions were extracted. Adjuvant chemotherapy administration was a favorable prognostic factor (hazard ratio: 0.43, P = 0.04), and it significantly prolonged disease-specific survival compared with no adjuvant chemotherapy (5-year disease-specific survival: 78.8% vs. 51.8%, P = 0.008). Adjuvant chemotherapy prolonged disease-specific survival in patients with tumor size <8 cm (5-year disease-specific survival: 100% vs. 54.6%, P = 0.02); however, its efficacy decreased in those with tumor size ≥8 cm (5-year disease-specific survival: 68.7% vs. 42%, P = 0.09). After propensity score matching, adjuvant chemotherapy was significantly associated with good disease-specific survival ( P = 0.02). Conclusions: Metastasis in the initial presentation was the poorest prognostic factor. On evaluating localized and resectable cases only, adjuvant chemotherapy significantly improved disease-specific survival, although its effect decreased in cases with large tumors. Abstract : Metastasis upon initial presentation was the poorest prognostic factor in patients with undifferentiated pleomorphic sarcoma of bone. Adjuvant chemotherapy improved disease-specific survival of patients with localized and resectable tumors.